Antibiotic Resistance Patterns of Pseudomonas aeruginosa in Respiratory Infections: Polanya Resistensi Antibiotik Pseudomonas aeruginosa pada Infeksi Pernafasan - Riyam Wissam Hassan (Academia Open, 2026)
General Background: Respiratory tract infections remain a major cause of morbidity worldwide and are frequently associated with bacterial pathogens. Specific Background: Pseudomonas aeruginosa is a prominent hospital-acquired pathogen known for its multidrug resistance, complicating therapeutic management. Knowledge Gap: Local and time-specific data on antibiotic susceptibility patterns of P. aeruginosa in respiratory infections remain limited. Aims: This study aimed to isolate and identify P. aeruginosa from sputum samples of patients with respiratory tract infections and to evaluate its antibiotic susceptibility patterns. Results: Out of 110 sputum samples, 78 showed bacterial growth, with P. aeruginosa identified in 26 samples (33.33%). High resistance rates were observed for cephalosporins, particularly ceftazidime (76.92%) and cefepime (73.07%), as well as levofloxacin (76.92%). Moderate resistance was noted for carbapenems, while higher sensitivity was recorded for amikacin (61.53%) and colistin (53.84%). Novelty: The study provides recent localized data on resistance profiles of P. aeruginosa in Al-Diwaniyah Governorate. Implications: These findings support evidence-based antibiotic selection and highlight the necessity for continuous surveillance to guide effective treatment strategies and limit antimicrobial resistance. Keywords: Pseudomonas Aeruginosa, Respiratory Tract Infections, Antibiotic Resistance, Sputum Samples, Antimicrobial Susceptibility Key Findings Highlights: Pseudomonas aeruginosa accounted for one-third of culture-positive respiratory samples. High resistance was observed against third- and fourth-generation cephalosporins. Amikacin and colistin showed comparatively higher susceptibility rates.